Upaya Peningkatan Kemampuan Guru Dalam Pembuatan RPP Melalui Supervisi Akademik Pada SMP Mardi Waluya 2 Kota Sukabumi - Fatimah, Atim (FKIP Universitas Muhammadiyah Sukabumi, 2018)
Lesson plan is an action plan of a face to face learning activity in a meeting or more. Alesson plan is developed from syllabus to guide students’ learning activities in achieving basiccompetence. In doing the teaching learning activity, it must refer to process standard but today thereare still many teachers in many schools who cannot compose a good lesson plan. The problemformulations in this research are whether by academic supervision, teachers’ ability in composinglesson plan can increase and whether teachers’ and school’s awareness in composing lesson plan canincrease too. The purpose of this research is to identify the influence of academic supervision toteachers’ and school’s ability and awareness in composing a lesson plan. This research was done intwo cycles. Steps in each cycle there were planning, implementation, observation, and reflection. Theresult of this research is that academic supervision can increase teachers’ ability in composing alesson plan and it can increase teachers’ and school’s awareness in composing a lesson plan.